The Benefits of Certification in Developing Teacher Professionalism in Efforts to Improve Teaching Quality - Papayosa, Emia; Amini, Aisyah; Syahfitri, Auliana; Habibi, Risky; Oktandi, Arif Hasim (Proceeding International Seminar of Islamic Studies, 2023)
The government has officially declared that the teaching profession is aligned with other professions as professionals. With this it is expected to improve the quality of education because the teacher as a learning agent is the spearhead of improving the learning process in the classroom which will lead to an increase in the quality of education. Recognition of the teacher's position as a professional is evidenced by a teacher's professional certificate obtained through a certification test. An educator certificate is given to teachers who have met the requirements as professional teachers.